Efficiency of Fertilization Through A Combination of Pseudomonas Fluorescens and NPK Fertilizer On Pre-Nursery Growth of Oil Palm Seedlings - Faizal Shofwan Kusnendi; Feri Rizki Nanda Marpaung; Ebenezer Muaratama Sibarani; Fransiska Natalia Purba; Danar Hadisugelar; Asyhar Sururi Juniawan (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2026)
Purpose : This study aimed to evaluate the extent to which Pseudomonas fluorescens can support the growth of oil palm seedlings while reducing the required dosage of inorganic NPK fertilizer. Methodology: The experiment was conducted in the greenhouse of the Plantation Crop Production Technology Study Program, Citra Widya Edukasi Oil Palm Polytechnic. A factorial experiment was arranged in a Completely Randomized Design (CRD) with several treatment levels of P. fluorescens and NPK. Results: The findings revealed that NPK fertilization had a significant effect on the growth of oil palm seedlings, whereas the sole application of Pseudomonas fluorescens showed no significant effect on the observed parameters. Conclusion: The application of Pseudomonas fluorescens had no significant effect on all observed parameters, except for stem diameter at 8 weeks after planting (WAP). NPK fertilizer did not affect stem diameter but significantly influenced plant height at 3 and 5 WAP, as well as leaf number increment at 12 WAP. The combination of Pseudomonas fluorescens and NPK fertilizer showed no significant interaction. Nevertheless, the combined use of Pseudomonas fluorescens and NPK fertilizer is expected to enhance fertilization efficiency and promote seedling growth in a more environmentally friendly manner. Type of Paper : Research article